Gestão da diversidade no Brasil: apresentação de um modelo brasileiro - Saji, Genilda Sandra Madeira (2010)
Made available in DSpace on 2010-04-20T20:20:33Z (GMT). No. of bitstreams: 1 107942.PDF: 378395 bytes, checksum: d9650cf89ebf35e26adffebb7c609fb7 (MD5) Previous issue date: 2005-06-30T00:00:00Z === This work presents the concepts of diversity and its management, gotten in foreign and national literature on the subject; it presents a Brazilian scene in the treatment of the subject and investigates its application in Brazilian company of national capital through a case study. As result, this work identify a possible Brazilian model of management of the diversity and presents its restrictions. === Esse trabalho apresenta os conceitos de diversidade e seu gerenciamento, obtidos na literatura estrangeira e nacional sobre o assunto; apresenta um cenário brasileiro no tratamento do tema e investiga a sua aplicação em empresa brasileira de capital nacional por meio de um estudo de caso. Como resultado, identifica-se um possível modelo brasileiro de gestão da diversidade e apresenta suas restrições